PERFORMANCE ANALYSIS OF OPEN SOURCE STORAGE CLOUDS IN CLOUD COMPUTING (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
Cloud computing is one of the latest research area that helps in storing the information permanently on the servers and manages the different resources for the requested users to provide on-demand services. In order to create the more usable and economic value based cloud computing, the principles, goals and structure of the cloud engineering is of vital importance. The objective of this study is to analyze the CPU and memory performance of different open source clouds. We will use different open source cloud to measure the different performance metrics like CPU time for downloading and uploading of file, memory usage while downloading and uploading the file, standard deviation of CPU usage and standard deviation of memory usage.